(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The current environmental situation in the world and Ukraine confirms the need for an immediate change in the mindset of each individual and society as a whole, and the formation of environmental awareness and environmental culture. That is why environmental education for specialists and environmental awareness should become priority areas in the educational process of every developed country. The experience of European countries demonstrates the possibility of improving the state of the environment based on the principles of state environmental policy, a high level of environmental culture, and an active position of society in nature conservation activities. However, achieving a high level of environmental culture is impossible without the introduction of environmental education and environmental awareness. In recent years, particular importance has been attached to the development of environmental education and culture throughout the world, as it has become clear that one of the main reasons for the failure to implement the decisions of international environmental forums, agreements, and conventions on nature conservation is the low level of environmental culture among the majority of the planet’s population and the low level of environmental education and awareness, particularly among those who make important decisions. Developed countries have developed and are refining various programs and concepts for the development of environmental education, as well as programs and plans for training modern environmental specialists. In just the last few years, many manuals and textbooks, popular science and journalistic literature have been published, films have been made, and recommendations on environmental education have been developed. In most countries around the world, ecology has become a compulsory subject in all schools and higher education institutions, many higher education institutions have established departments or faculties specializing in ecology, and hundreds of national and international seminars, conferences, and congresses on ecology have been held. The main goal of environmental education in Ukraine should be to shape the environmental culture of individuals and society as a whole, to develop skills, fundamental environmental knowledge, environmental thinking, and awareness based on the attitude towards nature as a universal and unique value.